Analisis Dimensi Kualitas Jasa Terhadap Kepuasan Pelanggan Pada BPJS Ketenagakerjaan Cabang Magelang - Purwita Sari, Dian; Achsa, Andhatu (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2020)
Badan Penyelenggara Jaminan Sosial (BPJS) has the task of fulfilling the social protection needs of workers who are caused by work and is responsible for the welfare of the workers as well as guaranteeing the workforce to be able to meet the needs of a decent life. Indicators that can help are service quality. This is because the appropriate service quality will make an experience that can attract potential customers when they feel satisfied with the service and the quality of service is also the first benchmark that will be assessed by the customer. The study was conducted with the aim of analyzing the dimensions of service quality with customer satisfaction at the Magelang Branch BPJS Employment. This study uses descriptive qualitative which uses interviews, observation, and literature review as a method of collecting data. Respondents used were 10 respondents using probability sampling techniques. The period of time carried out in this research is between January - February 2020. The results of the analysis of service quality dimensions show that customer satisfaction can be influenced by the presence of five dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and tangibility, so that the quality of service given higher, then customer satisfaction is also increasing. In this case, the quality expected by the customer can affect the ability of good service or overall attitude and evaluation in the long term.